CERTAIN FERTILITY INDICATORS OF SOILS IN THE AGROTEXSERVIS AND CHBN MASSIFS OF BESHARIQ DISTRICT, FERGANA REGION (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the impact of salinization on the fertility indicators of irrigated meadow soils in the Beshariq district of Fergana region. According to the collected data, when studying the fertility indicators, it was found that soil fertility was positively affected, although an increase in the degree of salinization was identified. One of the fertility indicators of the studied soils, based on their mechanical composition, was found to be light, medium, and heavy sandy, with some areas being sandy. The article also discusses the need for specific agronomic measures to be implemented in these soils.